1981
DOI: 10.1111/j.1399-3054.1981.tb04507.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoot initiation in light‐ and dark‐grown tobacco callus: the role of ethylene

Abstract: Shoot‐forming tobacco (Nicotiana tabacum L. cv. Wisconsin 38) callus produces less endogenous ethylene than non‐shoot‐forming tissue cultured in the light (16 h photoperiod) or the dark. In shoot‐forming tissue more ethylene is produced early in culture (days 0–5) than later. Also dark‐grown tissue produces much more ethylene than light‐grown. On the basis of experiments in which (1) gaseous ethylene was added to or (2) CO2 removed from the flasks, (3) Ethrel (an ethylene releasing agent) and (4) 1‐aminocyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
0
3

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 19 publications
(10 reference statements)
8
28
0
3
Order By: Relevance
“…As occurred at the highest ACC concentration in this study, a scarce bud formation but enhanced bud development (higher PR) in media supplemented with ethylene has also been reported by other authors, e.g. Huxter et al (1981). Ethylene production has also been described as influencing the development of somatic embryos in several works that have reported regeneration through the embryogenic pathway (Ptak et al 2009;Lu et al 2011).…”
Section: Effect On Organogenesis Of Different Doses Of Ethylene Inhibsupporting
confidence: 64%
“…As occurred at the highest ACC concentration in this study, a scarce bud formation but enhanced bud development (higher PR) in media supplemented with ethylene has also been reported by other authors, e.g. Huxter et al (1981). Ethylene production has also been described as influencing the development of somatic embryos in several works that have reported regeneration through the embryogenic pathway (Ptak et al 2009;Lu et al 2011).…”
Section: Effect On Organogenesis Of Different Doses Of Ethylene Inhibsupporting
confidence: 64%
“…This hypothesis is supported by the findings of Huxter et al (4), who showed that the amount of ethylene evolved from NSF tobacco callus is significantly greater than that evolved from SF callus tissue. Exogenous ethylene supplied to light-grown SF callus significantly reduced the number of calli which formed shoots, depending on the concentration and time of application.…”
Section: Resultssupporting
confidence: 80%
“…1). A similar increase in the rate of ethylene production in NSF callus has been reported (4). Both the time-scale of this response (11,16) and the lack of a similar change in SF tissue suggest that the increasing concentrations of ACC in NSF tissue are not the result of wound formation during subculture.…”
Section: Resultssupporting
confidence: 55%
“…The presence of ethylene was found to be important for embryogenesis from anther cultures of Hordeum vulgaris (6) and flower bud formation from thin-layer explants of Nicotiana tabacum (28). In contrast, shoot regeneration from callus cultures of Helianthus annuus (18) and N. tabacum (10) was inhibited by ethylene. The use of EIs, e.g.…”
mentioning
confidence: 92%